Effect of proximal box elevation on fracture resistance and microleakage of premolars restored with ceramic endocrowns. - Hong Zhang; He Li; Qian Cong; Zhimin Zhang; Aobo Du; Ying Wang (PLoS ONE)
Background Restoration of endodontically treated premolar is in high risk for biomechanical failure, and often presents with subgingival margins. Proximal box elevation (PBE) has been used to relocate subgingival cavity outlines. Objective To evaluate the influence of PBE on fracture resistance and gingival microleakage of premolars with endodontic access cavities following ceramic endocrown. Methods Eighty sound maxillary premolars with standardized Class II cavities on mesial surfaces were randomly assigned to four groups (n = 20 in each group). Groups E1, E2 and E3, with proximal margins located in dentin/cementum, 2 mm below the cemento-enamel junction (CEJ), simulated subgingival location. Group E4 (supragingival group), with proximal margins located in enamel, 1 mm above the CEJ, was used as the positive control. For margin elevation of the proximal cavities, bulk-fill Smart Dentin Replacement (SDR), a visible light cured resin composite, was applied in group E1, and conventional resin composite (3M Z350 XT, a light-activated composite) was placed in group E2. Group E3 was only treated with a ceramic crown and served as the negative control. In all groups, computer-aided design (CAD) ceramic endocrowns were adhesively inserted, and fracture resistance, failure mode and microleakage were evaluated. Results A higher fracture resistance value was observed in PBE groups E1 and E2, regardless of the materials used (P = 0.038, and 0.010, respectively, vs E3), and fracture resistance in group E1 was higher than that in group E2. In teeth without PBE, the percentage of catastrophic failures reached 70%. Compared to group E3, a lower frequency distribution of microleakage was detected in supragingival group E4 (P = 0.031). No increased percentage of microleakage was observed in groups treated with PBE. Conclusion For endodontically treated maxillary premolars restored with ceramic endocrowns, PBE increases fracture resistance but not microleakage.